Characteristics of hemostasis system and activity of trypsin-like blood enzymes in comorbid patients with chronic obstructive pulmonary disease and hypertension. - O. M. Kovalenko; V. V. Rodionova (Medičnì Perspektivi)
This work was aimed at studying the activity of the hemostasis system and trypsin-like blood enzymes (TLE) in patients with chronic obstructive pulmonary disease (COPD) and hypertension (H), depending on anthropometric, clinical features and smoking. The study included 87 patients. I group included 39 patients with COPD A – D, II-IV by GOLD and concomitant with H I-II stage, II group  – 38 patients with H I - II stage, and K group  – 10   apparently healthy persons. The study was conducted on the background of the use of standard basic therapy by patients from the 1st and 2nd groups in a stable period of disease. The degree of thrombocyte (tr) adhesion in I and II groups of patients was higher than in the K group. Both adhesive activity and the amount of tr in the I group was higher than in the II group. With positive status of smoking and increasing nicotine addiction in comorbid patients with COPD and H, the adhesive activity of tr increased. The level of the procoagulantive parameters of the plasma part of hemostasis in the two studied groups was not statistically different, but was higher than in the K group. Increased BMR and dyspnoea by the mMRS scale in group with COPD and H and increased age of patients with H led to the increase in the activity of plasma coagulation factors. In I and II groups, the increase in blood TLE was observed, which increased with the body weight, while in comorbid patients in the subgroup with FEV1≥50%, the incidence of COPD exacerbation additionaly effects the increase of TLE. In I group correlation between reduction of FEV1 with the decrease of TLE was revealed. In patients with COPD and AH activity of thrombocyte and plasma hemostasis, as well as trypsin-like blood enzymes, increases. Smoking, body weight gain and incidence of COPD exacerbation contribute to increased prothrombotic potential.